Dinamika Psikologis Siswa Korban Broken Home Di SMA Negeri 10 Semarang - Renjana, Kidung Jamung; Suhendri, Suhendri (Universitas Pahlawan Tuanku Tambusai, 2024)
This research was conducted with the aim of knowing the psychological dynamics of students who are victims of broken homes at SMA Negeri 10 Semarang. This research uses a qualitative approach. Data collection techniques use observation, interviews and documentation techniques. The results of the research show (1) There was a divorce in MN's family and MN's mother was treated unfairly, causing MN to have a bad view of herself, her family, her parents and the trauma of her marriage. MN often feels sad and envious of other families and shows reactions of aggression, withdrawal, regression and compensation. Coping is done to try to avoid problems occurring. (2) The mother abandoned N when he was a baby, then the father remarried and did not receive good treatment from his stepmother without the father's knowledge. Often feel sad and cry. Shows emotional diversion, withdrawal, regression and compensation reactions. Coping is done by praying and praying so that he will soon be reunited with his biological mother. There has been no action from the family and the guidance and counseling teacher (3) L's parents decided to separate due to arguments between their parents, causing L to have a bad view of himself, his family and his parents. Feeling sad and disappointed in himself. Shows emotional diversion, withdrawal, regression and compensation reactions. So far L has chosen to remain silent and there has been no action from his family and guidance counselor.